Is There an Earth-like Planet in the Distant Kuiper Belt? - Lykawka, Patryk Sofia; Ito, Takashi (The Astronomical journal, 2023)
The orbits of trans-Neptunian objects (TNOs) can indicate the existence of an undiscovered planet in the outer solar system. Here we used N -body computer simulations to investigate the effects of a hypothetical Kuiper Belt planet (KBP) on the orbital structure of TNOs in the distant Kuiper Belt beyond ∼50 au. We used observations to constrain model results, including the well-characterized Outer Solar System Origins Survey (OSSOS). We determined that an Earth-like planet ( m ∼ 1.5–3 M ⊕ ) located on a distant (semimajor axis a ∼ 250–500 au, perihelion q ∼ 200 au) and inclined ( i ∼ 30°) orbit can explain three fundamental properties of the distant Kuiper Belt: a prominent population of TNOs with orbits beyond Neptune’s gravitational influence (i.e., detached objects with q > 40 au), a significant population of high- i objects ( i > 45°), and the existence of some extreme objects with peculiar orbits (e.g., Sedna). Furthermore, the proposed KBP is compatible with the existence of identified gigayear-stable TNOs in the 2:1, 5:2, 3:1, 4:1, 5:1, and 6:1 Neptunian mean motion resonances. These stable populations are often neglected in other studies. We predict the existence of an Earth-like planet and several TNOs on peculiar orbits in the outer solar system, which can serve as observationally testable signatures of the putative planet’s perturbations.